Laboratory Markers of Chronic and Acute Stress: Diagnostic Value and Clinical Implications (Part 1: Pathophysiology of Acute and Chronic Stress in the Context of Its Influence on Cardiovascular System) - Shkvarok-Lisovenko, Anastasiia; Bushman, Yevheniia (The Ukrainian Scientific Medical Youth Journal, 2025)
chronic stress significantly impacts human health by dysregulating the hypothalamic-pituitary-adrenal (HPA) axis and autonomic nervous system (ANS), leading to neuroendocrine, immunological and metabolic imbalances. Chronic hyperactivity of this system increases cardiac output, induces vasoconstriction, and raises blood pressure, gradually leading to vascular remodeling, myocardial hypertrophy and an elevated risk of cardiovascular events. To explore the diagnostic and pathophysiological significance of neuroendocrine biomarkers in the assessment of stress and its influence on the cardiovascular system. A comprehensive literature review of 76 literature sources in English was conducted using PubMed, Scopus, Web of Science and Google Scholar, focusing on the relationship between the hypothalamic-pituitary-adrenal (HPA) axis, the autonomic nervous system (ANS) and chronic stress; the search included peer-reviewed publications from 2020 to 2025 with keywords including “acute stress”, “chronic stress”, “HPA axis dysregulation”, “autonomic nervous system”, “chronic stress”, “cortisol”, “epinephrine”, “norepinephrine”, “dehydroepiandrosterone”, “dopamine”, “aldosterone”, “tumor necrosis factor alpha”, “interleukin-1”, “interleukin-6”, “C-reactive protein”, “insulin-like growth factor-1”, “cholesterol”, “albumin”, “glycosylated hemoglobin” and “cardiovascular system”; the inclusion criteria encompassed original research studies, systematic and narrative reviews, meta-analyses and clinical guidelines; non-peer-reviewed sources and publications not in English were generally excluded. Neuroendocrine biomarkers provide essential insights into the physiological burden of stress and the functioning of the HPA axis and ANS. Cortisol remains the most established biomarker for both acute and chronic stress, with hair cortisol offering unique advantages for long-term assessment. Catecholamines reflect acute sympathetic activation, but their diagnostic value in chronic stress is limited. Neuroendocrine markers enhances clinical decision-making and may support personalized strategies in stress-related diseases prevention and management. Early detection of elevated neuroendocrine markers associated with chronic stress may provide valuable insight into the mechanisms underlying increased cardiovascular risk and support more effective management of patients with cardiovascular disease.